2013
DOI: 10.1111/bij.12211
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to elaboration of sexual dimorphism in bird plumage patterns

Abstract: Patterns, such as bars and spots, are common in birds. Some patterns can function in camouflage and/or communication and can benefit both males and females, paving the way for elaboration in sexual dimorphism. Historically, sexual dichromatism was predominantly considered to be a consequence of mating systems. However, the distribution of traits between the sexes is not always indicative of function; genetic correlation may cause traits to evolve in both sexes and traits may serve a social function in males an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 78 publications
1
39
0
Order By: Relevance
“…Alternatively, similarity in plumage coloration between the two sexes might simply be a genetically correlated response in one sex, male or female, to selection in the other sex (Lande , Roulin and Jensen , but see Gluckman ). In such a case, one would expect to observe a negative relationship between fitness and the intensity of plumage coloration in one sex and a positive one in the other one (Fitzpatrick et al , Roulin et al ), if color entails production or maintenance costs, which may be the case with iridescent colors (Dyck , Eliason and Shawkey , Meadows et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, similarity in plumage coloration between the two sexes might simply be a genetically correlated response in one sex, male or female, to selection in the other sex (Lande , Roulin and Jensen , but see Gluckman ). In such a case, one would expect to observe a negative relationship between fitness and the intensity of plumage coloration in one sex and a positive one in the other one (Fitzpatrick et al , Roulin et al ), if color entails production or maintenance costs, which may be the case with iridescent colors (Dyck , Eliason and Shawkey , Meadows et al ).…”
Section: Discussionmentioning
confidence: 99%
“…observ.). Among modern birds, the most elaborate tail morphologies are phylogenetically derived (Gluckman, 2014); however, Feitianius falls within the large polytomy of basal enantiornithines (Fig. 5), which may suggest that this clade began to experiment with different plumages fairly early in its diversification.…”
Section: Discussionmentioning
confidence: 99%
“…Although currently enantiornithines do not approach the skeletal diversity encompassed within Neornithes (O'Connor and , the new specimen suggests that the caudal plumages of these archaic birds may have reached levels of complexity comparable to those of extant taxa. This is unsurprising considering a recent study that suggested that plumage is highly evolutionarily labile, as inferred from the number of times that exaggerated features have independently evolved among closely related modern birds (Gluckman, 2014). The O'Connor et al-New enantiornithine Feitianius (e1054035-10) diversity of ornamental tail morphologies within Enantiornithes, which more closely approaches modern complexity and diversity than does the morphology of the skeleton, strongly suggests that sexual selection was a major driver of the diversification of feather and plumage morphologies during the early evolution of Aves.…”
Section: Discussionmentioning
confidence: 99%
“…, ; Roulin and Ducrest ; Nordeide et al. ; Gluckman ). Given that there is a large body of evidence linking pattern type with function, we focus solely on the type of pattern present in each species regardless of the sex.…”
Section: Methodsmentioning
confidence: 99%